Beyond Policy: The Use of Social Group Appeals in Party Communication. (4th May 2022) - Huber, Lena Maria
ABSTRACT: Extant research points to the importance of social identity and group attitudes for political behavior. Even though this should have important consequences for political communication, few scholars have investigated how parties use appeals to social groups to capitalize on these predispositions. This study introduces the concept of social group yield as a new theoretical framework to explain how parties strategically emphasize groups to mobilize their core voters and broaden their support base among the general electorate. Empirically, I examine the case of Austria based on a content analysis of electoral manifestos for the national elections in 2013, 2017, and 2019 to measure parties' group emphasis, combined with cross-sectional survey data measuring voters' group attitudes. The results confirm that group attitudes of party supporters and the wider electorate direct parties' emphasis of different groups. These findings have important implications for the representation of social groups, political polarization, and party competition.